Assessing the impact of personal income tax reforms on the income inequality dynamics in Russia in the 21st century - M. L. Dorofeev (Вестник университета)
The problem of regulating economic inequality to ensure social justice in society in the context of accelerating economic growth is of constant and obvious relevance. However, this problem does not have universal solutions due to significant country differences and the peculiarities of the social contract in a particular country. The purpose of this study is to analyse and assess the impact of reforms in the system of taxation of personal income on the dynamics of income inequality of Russian households. Dismantling the progressive personal income tax rate did not lead to a significant increase in income inequality in Russia, but the problem of excessive property inequality persisted until the beginning of 2022. The passive policy of regulating economic inequality unexpectedly yielded results in 2022. We expect, that after illegal confiscations and freezing of Russian assets abroad, coupled with anti-poverty programmes, the level of income and property inequality in Russia will significantly decrease on the horizon of 2022−2024. In the long term, the policy of passive financial regulation of inequality can produce a result that remains to be seen on the reporting data of Rosstat and international databases. In the future, when solving the dilemma between equality and economic growth, Russia should focus on the latter and make efforts to restore and then accelerate the growth of the average standard of living in the country.